Energy efficient cluster-based protocol for wireless sensor networks (WSN) - Samir, Bennane (2009)
The development of genetic algorithm to improve the performance of Leach (Low Energy Adaptive Cluslering Hierarchy) is presented in this thesis Genetic algorithm (GA) used in Leach is known as Leach-GA. In the proposed work. Initialization. Population. crossover. mutation and fitness function are calculated based on 100 nodes. Two types of protocols namely Leach and Leach-C are compared with Leach-GA. A routing protocol of LEACH and LEACH-C do not enable local computation to reduce the amount of the data that needs to be transmitted to the base station. A networking simulator known as NS-2 is used to validate the proposed algorithm. LEACH-GA was found to be more efficient than LEACH-C which deliver about 20% more data per unit energy than LEACH-C. This is because the genetic algorithm has more effective calculations rather than simulated annealing which is round to be in LEACIH-C and inherently produces less data for transmission.